2012
DOI: 10.4236/ojss.2012.24040
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hardness as an Indicator of Soil Strength of Agricultural Soils

Abstract: Soil strength is an important quality of agricultural soils prone to traffic. Surface hardness (SH) measured by the clegg impact tester (CIT) was evaluated as an indicator for assessing soil strength. Proctor tests were performed on a diverse range of soils to examine the relationships between bulk density (BD), penetration resistance (PR), SH and water content. All three indices showed typical response curves with increasing water content, with notable differences among the soils. Maximum dry bulk density (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…As explained by Bhagat (2003) initially lowest BD (1.62 g/cm 2 at 1WAT) was due to the submergence prior to tillage and it increased with time up to 1.81 g/cm 2 (12 WAT) which recorded as the highest, when the puddled soils undergo desiccation because of soil shrinkage. As reported by Eudoxie, et al (2012), this may be due to the MC variation of the field which showed the highest significant correlation (r = -0.893).…”
Section: Soil Propertiessupporting
confidence: 51%
“…As explained by Bhagat (2003) initially lowest BD (1.62 g/cm 2 at 1WAT) was due to the submergence prior to tillage and it increased with time up to 1.81 g/cm 2 (12 WAT) which recorded as the highest, when the puddled soils undergo desiccation because of soil shrinkage. As reported by Eudoxie, et al (2012), this may be due to the MC variation of the field which showed the highest significant correlation (r = -0.893).…”
Section: Soil Propertiessupporting
confidence: 51%
“…Christians [5] noted that the leaves of ZG are stiff, due to their high silica content [42], which could buffer the compactive force applied to the surface [43]. Eudoxie et al [44] also reported that the type of turfgrass cover influenced the effects of compaction on the bulk density of the underlying root zone. Statistically, root zone BD under ZG was similar for all stress treatments, supporting the argument that the root system of this grass may also be responsible for this result.…”
Section: Bulk Densitymentioning
confidence: 99%
“…As reported by Bhagat et al (1999) initially lowest BD (1.323 g/cm 3 at 1WAT) is due to the submergence prior to tillage and it increased with the time up to 1.7 g/cm 3 (12 WAT) which recorded as the highest, when the puddled soils shrink due to desiccation. As indicated by Eudoxie et al (2012), this may be due to the MC variation of the field which showed the significant correlation (r = -0.574) at 0.05 α level. As discussed by Grossman and Reinsch (2002), this average BD is in the reference range of agricultural soils.…”
Section: Soil Propertiesmentioning
confidence: 97%
“…3, the predicted and measured SS values show higher linear relationships (R 2 =0.695 in T 3 and 0.794 in other treatments). As reported by Eudoxie et al (2012), MC is identified as the determinant of surface soil strength of upland soils and Weerasooriya et al in (2015); MC and BD are identified as the determinants of surface compression strength of low land pudddled soil. These are partially supportive findings to this result.…”
Section: Relationship Between Ss and Other Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation